2009
DOI: 10.1159/000228928
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Drug Use in a New Generation of Problem Drug Users in Amsterdam: a 6-Year Follow-Up Study

Abstract: Aims: This study describes the transitions in drug use in Amsterdam among young drug users (YDUs) who are inhaling or injecting cocaine or using illicitly obtained opiates. Methods: From 2000 until 2003, 187 YDUs (≤30 years) were recruited of whom 126 were followed into 2007. Results: During the 6 months prior to inclusion, 95% used cocaine, 60% used illicit opiates, and 9% injected more than once a week. During follow-up, the incidence of new-onset heroin use was 4.8/100 person-years. The incidence of injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…3,10 In the present study, reported use of other substances, both ever in life and in the previous year, confi rmed this tendency, even though we were unable to clearly establish how these associations operate or their meaning.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…3,10 In the present study, reported use of other substances, both ever in life and in the previous year, confi rmed this tendency, even though we were unable to clearly establish how these associations operate or their meaning.…”
Section: Discussioncontrasting
confidence: 59%
“…Notwithstanding, long-term follow-up studies of the consequences of crack cocaine use are still scarce. 3,7 A topic of interest in recent years has been the longevity of crack cocaine use among treated and nontreated users, especially given its intensity, recurrence, and, in many cases, persistence. 13 These studies indicate that the use of crack cocaine is no longer an essentially short-term practice.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of compulsive use of crack and of other drugs might be defined as the daily intake, during up to nine consecutive days, and that generally only ends when the user reaches the physical, mental or financial exhaustion The use of multiple drugs associated with crack, characteristic often observed among crack users 19 , can hinder the suitable identification of disorders resulting from the use of existing substances, thus serving as a confounding factor in relation to the interference of a certain substance on health, in addition to hampering the treatment adherence and its respective success.…”
Section: Didn't Kept Control Of Myself I Started Smoking 'Mesclado' mentioning
confidence: 99%
“…Another, much smaller, figure was cited by Langendam et al [34] , who found a one-year cessation rate of 4.1 per 100 person-years, varying with calendar time. In a 6-year follow-up study of problem drug users in Amsterdam, the transition to abstinence or nonfrequent drug use was 23 per 100 person-years [35] . An 8-year follow-up study of young injection drug users from San Francisco reported an injection cessation rate of 16.4 per 100 person-years [36] .…”
Section: Entry To Hard Drug Usementioning
confidence: 99%